PENERAPAN MEDIA LITERASI DIGITAL DALAM MENINGKTKAN KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS IV SD NEGERI 147 PELALI KABUPATEN ENREKANG - Laman, Almaida; Tasrif Akib; Nur Khadijah Razak (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Almaida Laman. 2026. Implementation of Digital Literacy Media to Improve Reading Comprehension Skills of Fourth-Grade Students at SD Negeri 147 Pelali, Enrekang Regency. Thesis. Elementary School Teacher Education Study Program, Faculty of Teacher Training and Education, Muhammadiyah University of Makassar. Supervisor I: Tasrif Akib and Supervisor II: Nur Khadijah Razak. This research was motivated by the low reading comprehension skills of fourth-grade students at SD Negeri 147 Pelali, Enrekang Regency. Based on initial observations, approximately 43% of 23 students had not achieved the learning mastery standard (KKTP) of 75 and the minimum classical mastery standard (80%). Students still experienced difficulties in understanding reading content, such as finding the main idea, answering questions based on the text, and summarizing the reading. Furthermore, learning methods that still use conventional methods make students less active and less interested in reading activities. This research aims to improve students' reading comprehension skills through the application of digital literacy media. The research used was classroom action research, conducted in two cycles, each consisting of planning, implementation, observation, and reflection. The subjects were 23 fourth-grade students. Data were collected through observation, achievement tests, documentation, and interviews. Data were then analyzed qualitatively and quantitatively, assessing the percentage of student activity and learning completion. The results showed that the application of digital literacy media improved students' reading comprehension. In the first cycle, student activity began to increase, with 67% paying attention to teacher explanations, 61% using digital media, 57% reading texts, 52% asking questions, 61% answering questions, 57% finding the main idea, 52% summarizing the reading content, and 65% working in groups. However, learning completion was not achieved. After improvements were made in Cycle II, student activity and learning outcomes improved significantly, with at least 80% of students achieving grades above the 75 minimum competency standard (KKTP). Therefore, the implementation of digital literacy media is effective in improving students' reading comprehension skills because it makes learning more engaging, helps students understand the content of the reading, and increases their active participation in the learning process.